Advancements in the endoscopic treatment of pancreatic fluid collections - Jing Li (KeAi Communications Co., Ltd., 2020)
Endoscopic drainage of pancreatic fluid collections (PFCs) with fewer complications and less trauma has gradually replaced surgery or percutaneous drainage to become the first-line treatment for PFCs. In recent years, the differential efficacy of various stent techniques to drain different types of PFCs has been controversial. This review summarizes the clinical applications of endoscopic ultrasound-guided stent placement for PFCs drainage.